Distal phalanx: an unusual site for a gastric adenocarcinoma metastasis. Issue 9 (9th September 2020) - Harris, Holly; Khan, Mansoor; Jaunoo, Shameen
Abstract : Gastric adenocarcinoma typically metastasises to the liver, peritoneum and lung. Bone metastasises are less frequent and particularly uncommon in the distal extremities. This is an unusual case of metastatic disease in the distal phalanx mimicking the presentation of osteomyelitis. This case highlights the need to remain vigilant in patients with known cancer and to always be mindful of metastatic disease, even if the presentation is atypical.